Sistem Informasi Manajemen Bengkel Bowo Motor Sragen - Ega Bangun Saputro; Robby Rachmatullah (Go Infotech: Jurnal Ilmiah STMIK AUB, 2017)
Bowo’s Motorcycle Workshop is one of workshop that supply motorcycle spareparts and give a service of motorcycle in the Sragen city. Bowo’s Motorcycle Workshop have  a vision to become a workshop who be able to provide maximum service to their customers. Bowo’s Motorcycle Workshop problems are on processing of data spareparts when the stock data warehouse not matching with inventory book and give impact on the slow process to obtain information about spareparts data. Other than that customer service’s problems regarding the queue of customers also have a problem in the order of handling services, so many customers feel disappointed about length of queue service at Bowo Motor Workshop. So to resolve these problems it is necessary to build a Management Information System. In this research, this system is builded based on desktop VB.NET as a software development tool (development tool), and MySQL as a database. System development method use waterfall model with step analysis system requirement, system design, writing program code, testing with blackbox method, implementation and maintenance. This system is built to give convenience for the Bowo Motor Workshop to obtain information on spareparts data management. This system also provides convenience to the customer service’s Workshop Bowo Motor in managing the queue of services Bowo Motor Workshop and customers can directly monitor the number of queues that exist. So the management Information System in Bowo’s Motor Workshop is able to advance the vision on the Bowo’s Motor Workshop for provide maximum service to the customers. Keywords: Management Information System, Bowo’s Motorcycle Workshop, Queue